2014
DOI: 10.1093/molbev/msu338
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene Australian Marsupial DNA Clarifies the Affinities of Extinct Megafaunal Kangaroos and Wallabies

Abstract: Understanding the evolution of Australia's extinct marsupial megafauna has been hindered by a relatively incomplete fossil record and convergent or highly specialized morphology, which confound phylogenetic analyses. Further, the harsh Australian climate and early date of most megafaunal extinctions (39-52 ka) means that the vast majority of fossil remains are unsuitable for ancient DNA analyses. Here, we apply cross-species DNA capture to fossils from relatively high latitude, high altitude caves in Tasmania.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 63 publications
5
26
0
Order By: Relevance
“…Most of these fragments are within the size range expected for M. rufogriseus and V. ursinus, but two bones were a closer match for Macropus giganteus in size (Garvey, 2006). Biomolecular methods hold great potential for identifying nondescript bone fragments to species, as has been demonstrated recently in Australia using ancient DNA (aDNA)-based methods (Murray et al, 2013;Grealy et al, 2015;Llamas et al, 2015). Nevertheless, archaeological and palaeontological sites with good aDNA preservation are rare in non-frozen landscapes (Poinar and Stankiewicz, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these fragments are within the size range expected for M. rufogriseus and V. ursinus, but two bones were a closer match for Macropus giganteus in size (Garvey, 2006). Biomolecular methods hold great potential for identifying nondescript bone fragments to species, as has been demonstrated recently in Australia using ancient DNA (aDNA)-based methods (Murray et al, 2013;Grealy et al, 2015;Llamas et al, 2015). Nevertheless, archaeological and palaeontological sites with good aDNA preservation are rare in non-frozen landscapes (Poinar and Stankiewicz, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We have also shown that the DNA fragmentation at RCEC is not entirely dependent on age, meaning that the DNA loss in megafaunal bones from the older layers may have been slower than the younger layers. Improvements in DNA technology such as target enrichment through hybridization capture and higher sequencing coverage may improve the chances of retrieving low‐copy number DNA (Llamas et al ., ), particularly mtDNA. Post‐excavation conditions will also influence the retrieval of aDNA.…”
Section: Resultsmentioning
confidence: 97%
“…At these sites, aDNA preservation is clearly exceptional; in comparison, much shorter fragments were retrieved from much younger samples at RCEC. More recently, 37–121 unique mtDNA sequences averaging 37–40 bp were recovered from 40 000–50 000 cal a BP megafaunal bone from high altitude caves in Mt Cripps, Tasmania (Llamas et al ., ); however, no DNA was able to be amplified through PCR, and libraries were enriched for endogenous DNA. While there were too few endogenous sequences to estimate k for Layer 6, we still managed to retrieve mtDNA and nuDNA from bones over 18 000 years old without enrichment.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations